Відповідь:96.02-1.6√3
Пояснення:(4√6-0.1√2)^2=16*6-2*4√6*0.1√2+0.01*2=96-0.8√12+0.02=96.02-0.8√12=96.02-1.6√3
task/30647175 Решить уравнение √(3x²- 4x+15) +√(3x²- 4x+8) = 7
решение ОДЗ : x ∈ ( - ∞ ; ∞ ) , т.к.
3x²- 4x+8=3(x -2/3)²+20/3 ≥ 20/3 > 0 || D₁=2² -3*8 = -24 < 0 || следовательно и 3x²- 4x+15 = ( 3x²- 4x+8 ) + 7 > 0 * * * 3(x -2/3)² +41/3 ≥ 41/3 * * *
замена : t = 3x²- 4x+ 8 ≥ 20/3 ; √(t +7) + √t =7 ⇔√( t +7 ) = 7 - √t
возведем обе части уравнения √( t +7 ) = 7 - √t в квадрат
* * * необходимо 7 - √t ≥ 0 ⇔ √t ≤ 7 ⇔ 0 ≤ t ≤ 49 * * *
t +7 = 49 -14√t + t ⇔ 14√t = 42 ⇔ √t =3 ⇔ t = 9 || 7 - √t = 4 >0 ||
3x²- 4x+8 = 9 ⇔ 3x²- 4x -1 =0 ; D₁ = 2² -3*(-1) =7= (√7)²
x₁ =(2 -√7) / 3 ; x₂ = (2+√7)/3 .
ответ : (2 ±√7)/3 .
96.02 - 1.6√3
Объяснение:
(4√6 - 0.1√2)² = (4√6)² - 2 · 4√6 · 0.1√2 + (0.1√2)² = 16 · 6 - 0.8√6√2 + 0.01 · 2 = 96 - 0.8√12 + 0.02 = 96.02 - 0.8√12 = 96.02 - 0.8√(2 · 2 · 3) = 96.02 - 0.8 · 2√3 = 96.02 - 1.6√3